1999
DOI: 10.2307/3434419
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos and Cancer: An Overview of Current Trends in Europe

Abstract: This review assesses the contribution of occupational asbestos exposure to the occurrence of mesothelioma and lung cancer in Europe. Available information on national asbestos consumption, proportions of the population exposed, and exposure levels is summarized. Population-based studies from various European regions on occupational asbestos exposure, mesothelioma, and lung cancer are reviewed. Asbestos consumption in 1994 ranged, per capita, between 0.004 kg in northern Europe and 2.4 kg in the former Soviet U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 25 publications
(37 reference statements)
2
35
0
3
Order By: Relevance
“…The number of mesotheliomas in the industrial nations is still growing [75,4]. The data of the German mesothelioma register show the same trend.…”
Section: Introductionsupporting
confidence: 54%
“…The number of mesotheliomas in the industrial nations is still growing [75,4]. The data of the German mesothelioma register show the same trend.…”
Section: Introductionsupporting
confidence: 54%
“…An increased mortality rate due to malignant mesothelioma (MM) was documented in many European nations and Italy during the 1990s that was related to the massive spread of asbestos used during the 1950s and the 1960s (Albin et al 1999;Comba et al 2005;Bianchi and Bianchi 2007). Some authors have estimated that the growing incidence of this tumor observed in the last decades will reach a peak between 2010 and 2020 (La Vecchia et al 2000;Marinaccio et al 2005;Pannelli et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Further increases in lung cancer due to asbestos exposure are expected for the near future [11][12][13]. Combining the risk of developing lung cancer from asbestos and smoking leads to a multiplication of the risk of developing lung cancer [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%